Micropaleontologia da litofácies recifal da formação pirabas (mioceno inferior), praia do Maçarico, Município de Salinópolis, Estado do Pará - SOUZA, Bruna Leal Passos de (2019)
This work presents the resulting data from microfossils analysis of the Pirabas Formation reef lithofacies, exposed in The Maçarico beach, Salinópolis city, state of Pará. This fossil bioherma developed on the inner shelf of Pirabas sea, with lenticular shape, small dimensions and peculiar diagenetic aspects. Samples of the three ecological succession stages were colected for foraminifera, ostracodes and bryozoans sorting, so that palaeoenvironmental interpretrations could be done. The obtained data indicates the bioherma developed in warm shallow waters, with high energy, sedimentation rate low to moderate and high availability of nutrients and calcium carbonate. The species diversity is low and the specimens are scarce due the intense diagenesis caused the dissolution of the many biotic elements.